Interactive Multimedia in Shallow Foundation Support Capacity Material - Riyan Arthur; Erna Septiandini; Nousseva Renna (Universitas Pendidikan Ganesha, 2022)
Education needs to be modernized so that it is in line with technological developments, for example, interactive multimedia that can be accessed through digital devices such as computers/laptops. Some of the factors that are problematic in learning are limited learning time in the classroom, difficult materials abstract material, limitations on tools and media as well as low learning motivation. Learning media need to be chosen appropriately in accordance with the objectives and learning materials so that they can be used effectively and efficiently to achieve learning objectives. The purpose of this research is to produce a product in the form of Interactive Multimedia on the material shallow foundation support capacity in the Building Engineering Education Study Program. The method of this research is research and development (R&D) method with the ADDIE model consisting of the stages of analysis, design, development, implementation, and evaluation. The interactive multimedia that was developed got 80.7% with the proper category by material experts and 79.4% with the proper category by media experts. Based on the results of the limited trial, there was an increase in the average value of the pre-test by 54.5 and the post-test by 79.75. The results of validation by material experts and media experts as well as limited trials show that interactive multimedia that has been developed is declared feasible and ready to be implemented in the material shallow foundation support capacity.